The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/anec.12274
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Power of f99 Repolarization Index for the Occurrence of Ventricular Arrhythmias

Abstract: The f99 represents a promising risk index for the occurrence of ventricular arrhythmias, especially when maximized over the three orthogonal leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Therefore, to light of results, the use of HRS_BH3 is appropriate for sport applications relying on MHR estimations, but not to clinical evaluations based on HRV measurements. Instead, ECG_BH3, although sampled at a frequency (200 Hz) that is lower than that characterizing modern ECG machine (typically over 1000 Hz), can provide useful clinical information, allowing computation of both HR and repolarization parameters such as QT interval [20] Twave alternans [21,22] and f99 [23]. Still, there are several important differences between BH3 and traditional clinical ECG devices.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to light of results, the use of HRS_BH3 is appropriate for sport applications relying on MHR estimations, but not to clinical evaluations based on HRV measurements. Instead, ECG_BH3, although sampled at a frequency (200 Hz) that is lower than that characterizing modern ECG machine (typically over 1000 Hz), can provide useful clinical information, allowing computation of both HR and repolarization parameters such as QT interval [20] Twave alternans [21,22] and f99 [23]. Still, there are several important differences between BH3 and traditional clinical ECG devices.…”
Section: Discussionmentioning
confidence: 99%
“…Development of a CaRiSMA 1.0 app providing alarms in real time is in progress. Future versions of CaRiSMA using other innovative ECG risk indexes such as T-wave alternans and f99 [20,42,43], besides QTc, are also under evaluation.…”
Section: Carisma 10 Softwarementioning
confidence: 99%
“…Nevertheless, neither LVEF [16] nor the aforementioned indexes have proven sufficiently reliable for SCD prevention [4,5,[16][17][18]. Thus, we recently introduced a new frequency-based repolarization index termed f99, which is defined as the frequency at which the repolarization normalized cumulative energy reaches or overcomes 99% [19][20][21]. Notwithstanding, although f99 was found able to discriminate ventricular arrhythmias [21], still its predictive power is not sufficient to justify preventive diagnostic and therapeutic procedures in previously asymptomatic patients [21].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we recently introduced a new frequency-based repolarization index termed f99, which is defined as the frequency at which the repolarization normalized cumulative energy reaches or overcomes 99% [19][20][21]. Notwithstanding, although f99 was found able to discriminate ventricular arrhythmias [21], still its predictive power is not sufficient to justify preventive diagnostic and therapeutic procedures in previously asymptomatic patients [21]. To overcome this issue, some authors have reported an increase in the predictive power when combining different indexes through various techniques [22,23], such as multiple linear regression or logistic regression (LR) [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation